Managing diversity: an assessment of the national question in Pakistan. Issue 2 (3rd April 2023) - Shah, Jamal; Khan, Bakhtiar
ABSTRACT: Modern societies are confronted with a plethora of issues that have far-reaching socio-political ramifications. The negative effects of diversity are primarily the result of state policies. Where societies were not homogenous, attempts were made to bring desperate populations together to advance official nationalist projects. Pakistan, being dominantly a Muslim state, has religio-cultural and ethnic diversity where minority groups have raised their voices against the unjust state's policies. This study examines how these issues evolved over the course of Pakistan's history. The paper attempts to answer the question 'why has Pakistan's plurality become unmanageable?' The results demonstrate that a high degree of centralization of authority, the adoption of Urdu as a national language, a sense of domination of the central institutions by the Punjabis, underrepresentation of ethnic minorities in state institutions, and controlled society has aggravated the position of diverse groups in Pakistan, with colossal consequences to national economy and social harmony.